Medicinal Chemistry and Target Identification of Synthetic Clinical and Advanced Preclinical Antimalarial Candidates (2000 - 2022) - Cheuka, Peter M.; Mambwe, Dickson; Mayoka, Godfrey (Current Topics in Medicinal Chemistry, 2023)
Background: The downward trend in malaria cases and deaths is steadily reversed - 627,000 deaths in 2020 compared to 405,000 deaths in 2018. Drug resistance has compromised the effectiveness of currently available treatment options, with some reports documenting molecular markers of resistance to artemisinins in African countries in addition to the Greater Mekong subregion, which was initially associated with this kind of resistance. Therefore, the development of novel drugs is crucial to replenishing the antimalarial drug arsenal toward malaria eradication. In this review, we summarize the progress made in antimalarial drug discovery in the period 2000 - 2022, focusing on drug candidates which have made it to advanced preclinical trials (drugs tested in rodent species and at least one higher species such as dog or monkey) and beyond. Methods: We searched Google Scholar and selected studies meeting these defined criteria. We highlight the medicinal chemistry optimization of these compounds; the preclinical/clinical evaluation and the mechanisms of action. Results and Conclusion: Although the pipeline seems promising, the prospect of having an antimalarial medicine that meets the current target product profiles (TPPs) towards the malaria eradication agenda is far from reality. Some of the key TPP attributes required include multistage activity, resistance- proof; ability to achieve a single dose cure and safety across a wide range of patient populations. Clinical trials are ongoing for some promising molecules, inspiring optimism toward identifying better drugs that meet these defined TPPs. Until then, concerted research efforts should continue to be mounted to populate the antimalarial drug discovery and development pipeline.
Keywords: Preclinical candidates